PENGGUNAAN METODE PROBLEM SOLVING MODEL POLYA PADA SOAL CERITA FPB DAN KPK - Ulfa, Maria; Ariani, Yetti; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThis research was motivated by students’ learning outcome were low on question of the story fpb and kpk. This study aimed to determine the effect of using problem solving model polya method on learning outcomes students of question story fpb and kpk. Then the design of the reasearch is quasi experiment with nonequivalent control group design. A sampel of the reasearch is V grades of SDN 05 Serasi Kecamatan Rao Selatan. Moreover, the result showed that there was an effect on using problem solving model polya  method. Last, the result t-test on α 0.05 and df 20, t hitung (3,37) ≥ t tabel (2.08) and also shown from the average obtained experimental class of 75,90 and average 49,22 control class.Keywords : problem solving model polya method, question of the story FPB and KPK, learning outcomes.